Vaginal cytology and cervical mucus as tools to predict ovulation time in small ruminants - Souza-Fabjan, Joanna Maria Goncalves; Brair, Viviane Lopes; Santos Silva, Dafne dos; Schmidt, Ana Paula Pereira; Figueira, Lucas Machado; Rangel, Paulo Sergio Cerqueira; Vergani, Gabriel Brun [UNESP]; Oliveira Machado, Vitoria de; Oliveira, Maria Emilia Franco [UNESP]; Fonseca, Jeferson Ferreira da (Springer, 2021)
The possibility of using cervical mucus and vaginal cytology as tools to predict ovulation time was assessed in 11 ewes and 11 does raised under tropical conditions. Every 12 h from progesterone removal to ovulation, estrus behavior, cervical mucus, vaginal cytology, and ovarian ultrasound exams were performed. In goats, vaginal cytology had 88% of accuracy on detecting the ovulation time. However, in sheep, there was no cell pattern in the vaginal cytology and cervical mucus varied at ovulation. In conclusion, both vaginal cytology and mucus evaluation may be useful tools to determine the ovulation time in goats; however, both strategies are less accurate in sheep.
Keywords: Goat; Ovulatory timing; Sheep; Ultrasound; Vaginal cells